Pelatihan Keterampilan Regulasi Diri dengan Perspektif Mindfulness (PKRM) bagi Guru untuk Mengatasi Masalah Mental Emosional Peserta Didik - Suzy Yusna Dewi; Nunuk Nugrohowati; Melly Kristanti; Yasmin Azizah Idhsa; Yaya Aria Santosa; Dinda Amalia Suryadi; Yunita M. Lestari (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Changes in the era of globalization plus the Covid-19 pandemic have caused problems in emotions and behavior, give an impact on the physical and psychological conditions of students. The purpose of study is to help reduce stress, emotion and anxiety problems, by educating and practicing to be applied in everyday life, carry out through online for all Nusantara Nature School Network teachers. The implementation was given to 96 Nature School Network teachers, then the MAAS & SSRQ Questionnaires and understandings were given out and two weeks later an evaluation was held. Most of the participants were elementary school teachers (75.8%), dominated by 85.3% women. The condition of self-regulation of mindfulness training participants at those teachers was the most with good self-regulation conditions of 93.3% with an average MAAS 46.10, SSRQ 99.42 and a total of 145.53. The level of understanding respondents after participating was 41.7% of who already understands the materials, not understands at 36.1%. There is better self-regulation with the teachers as training participants, the level of understanding of participants after follow the activities being quite good. Mindfulness training needs to be done regularly, so that teachers can apply mindfulness to students at school.